Hepatitis B plasmonic biosensor for the analysis of clinical serum samples - Riedel, Tomáš; Surman, František; Hageneder, Simone; Pop-Georgievski, Ognen; Noehammer, Christa; Hofner, Manuela; Brynda, Eduard; Rodriguez-Emmenegger, Cesar; Dostálek, Jakub (Biosensors & bioelectronics, 2016)
A plasmonic biosensor for rapid detection of protein biomarkers in complex media is reported. Clinical serum samples were analyzed by using a novel biointerface architecture based on poly[(N-(2-hydroxypropyl) methacrylamide)-co-(carboxybetaine methacrylamide)] brushes functionalized with bioreceptors. This biointerface provided an excellent resistance to fouling even after the functionalization and allowed for the first time the direct detection of antibodies against hepatitis B surface antigen (anti-HBs) in clinical serum samples using surface plasmon resonance (SPR). The fabricated SPR biosensor allowed discrimination of anti-HBs positive and negative clinical samples in 10min. Results are validated by enzyme-linked immunoassays of the sera in a certified laboratory. The sensor could be regenerated by simple treatment with glycine buffer.
Keywords: hepatitida B - antigeny povrchové; povrchové vlastnosti; protilátky virové; Equipment Design; povrchová plasmonová rezonance; Acrylamides; Polymer brushes; Surface Plasmon Resonance; Surface plasmon resonance; design vybavení; Biosensors; virus hepatitidy B; Hepatitis B; Hepatitis B Surface Antigens; Hepatitis B virus; limita detekce; lidé; Humans; Surface Properties; akrylamidy; hepatitida B; Limit of Detection; Antibodies, Viral; Antifouling; Blood serum